A case report of rare presentation of granulosa cell tumor with torsion and capsule rupture - Basavaraj, Nikhitha; Sasikala, R.; Varghese, Jessy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
We report a rare case of granulosa cell tumor (GCT) which has undergone torsion and capsule rupture presenting as acute abdomen. The incidence of ovarian torsion among women of reproductive age is 9.9 per 100,000 where dermoid cyst is more common to undergo torsion.